The international response to the outbreak of SARS in 2003 - Dominique Heymann (2004)
The sudden arrival of an internationally spreading outbreak of a newly identified infectious disease in early 2003, severe acute respiratory syndrome (SARS), provided an opportunity for a coordinated international response based on information and evidence obtained in real time through standard and electronic communications. Its containment represents a new way of working internationally, and demonstrates how intense collaboration in virology, clinical medicine and epidemiology can rapidly provide the information necessary to create and implement evidence-based control measures. The SARS outbreak serves as a reminder of the need for a strong national surveillance and response to infectious diseases, evidence-based international travel recommendations, and a global alert and response network to serve as a safety net when national surveillance fails.